Three Cases of Gastric Antral Vascular Ectasia in Chronic Renal Failure - Iguchi, Akira (S. Karger AG, 2011)
Gastric antral vascular ectasia (GAVE) is currently recognized as an important cause of gastrointestinal bleeding. Chronic kidney disease (CKD) is associated with a high incidence of GAVE. We report 3 patients with CKD who presented with severe anemia and were diagnosed with GAVE; they were resistant to endoscopic argon plasma coagulation. However, remission of anemia and improvement in GAVE lesions were observed after the initiation of hemodialysis. The pathogenesis of GAVE remains largely unknown, but mechanical stress of the antrum could play an important role. This stress may be reduced by hemodialysis through improvement of uremia-associated gastrointestinal symptoms. Therefore, the initiation of hemodialysis might be effective for intractable GAVE in CKD patients.